An Asymptomatic Male with Coexisting Celiac Disease and Primary Biliary Cirrhosis - Franzjosef Schweiger; Jasim Radhi (Canadian Journal of Gastroenterology)
Both primary biliary cirrhosis and celiac disease may be asymptomatic in many patients for extended periods of time. Rarely the disorders have been reported to occur together, in which case symptomatic malabsorption and diarrhea are virtually always present. An unusual case is presented of an asymptomatic male patient who had both primary biliary cirrhosis and celiac disease. The literature describing this coexistence, and theories regarding a common etiological link between the two disorders, are reviewed.